Implications of immunoglobulin G deposit in glomeruli in Chinese patients with diabetic nephropathy. Issue 7 (1st March 2020) - Zhang, Junlin; Zhang, Jie; Zhang, Rui; Wang, Yiting; Liang, Yan; Yang, Zhen; Wang, Tingli; Xu, Xuan; Liu, Fang
Abstract: Background: In the current study, we explored the associations of glomerular immunoglobulin G (IgG) deposit and further investigated the pattern of IgG subclass deposition in the renal biopsy specimens from patients with diabetic nephropathy (DN). Methods: A total of 170 inpatients with type 2 diabetes mellitus and biopsy‐proven DN who were followed up for at least 1 year were retrospectively recruited. Renal outcomes were defined by DN progression (end‐stage renal disease [ESRD] or ≥ 50% reduction in estimated glomerular filtration rate [eGFR] from baseline). Additionally, 38 renal biopsy specimens of patients with renal IgG deposit underwent the immunofluorescence IgG1‐4 staining. Results: The median follow‐up period was 22 months. During follow‐up, 38.23% (65) of patients progressed to ESRD, and 6.47% (11) of patients had an eGFR decline ≥50%. The multivariate Cox analysis demonstrated that the glomerular IgG deposit (hazard ratio, 1.835; 95% CI, 1.013‐3.324, P = .045) was still significantly associated with DN progression when adjusted for the important clinical variables and pathological findings. In addition, a logistic regression showed that the glomerular IgG deposit was independently associated with glomerular basement membrane (GBM) thickness (odds ratio [OR], 1.276; 95% CI, 1.046‐1.558; P = .016), Kimmelstiel‐Wilson nodules formation (OR, 3.822; 95% CI, 1.052‐13.881; P = .042), and C3 deposit in the glomeruli (OR, 124.883; 95% CI, 20.754‐751.472; P  < .001). The IgG subclass staining showed that IgG1 deposit along the GBM tended to be dominant (28/38) in IgG (+) patients with DN. Conclusions: The glomerular IgG deposit affected glomerular structure and emerged as an independent risk factor for the renal clinical outcomes. In addition, IgG1 predominantly deposited along the GBM among the DN patients with IgG (+), which might be involved in the renal injury and progression of DN. Abstract : Highlights This study included a large sample of type 2 diabetes mellitus patients who underwent renal biopsy and were followed‐up for more than 1 year. The implication of immunofluorescence in patients with diabetic nephropathy (DN) may have been overlooked by clinicians. In this study, we intended to pinpoint the association between the glomerular immunoglobulin G (IgG) deposit and the clinicopathological features and renal prognosis in patients with DN and further determine the patterns of the IgG subclass deposit on the kidney tissues. 摘要: 目的: 在本研究中, 我们旨在探索肾小球免疫球蛋白G (immunoglobulin G, IgG)沉积与糖尿病肾病(diabetic Nephropathy, DN)患者临床病理特征的相关性, 并进一步研究DN患者肾活检标本中IgG亚型分布特点。 方法: 回顾性纳入2型糖尿病合并病理确诊的DN且随访超过1年的患者170例。以进展至终末期肾病(end‐stage renal disease, ESRD)或估算的肾小球滤过率(estimated glomerular filtration rates, e‐GFR)下降超过基线≥50%为研究终点。另外, 对38例肾小球IgG沉积的DN患者的病理切片进行IgG1‐4免疫荧光染色。 结果: 随访中位时间为22个月。在随访期间, 38.23% (65例)的DN患者进展至ESRD, 6.47%(11例)的DN患者e‐GFR下降≥50%。多因素COX回归分析显示:在校正重要的临床因素及病理结果后, 肾小球IgG沉积仍然与DN进展显著相关(HR, 1.835; 95%CI, 1.013‐3.324, p=0.045)。另外, Logistic回归分析显示肾小球基底膜(glomerular basement membrane, GBM)厚度(OR, 1.276; 95%CI, 1.046‐1.558; p=0.016)、Kimmelstiel–Wilson结节形成(OR, 3.822; 95%CI, 1.052‐13.881; p=0.042) 以及肾小球C3沉积(OR, 124.883; 95%CI, 20.754‐751.472; p<0.001)与肾小球IgG沉积独立相关。IgG(+)DN患者的IgG亚型染色提示肾小球以IgG1在GBM沉积(28/38)为主。 结论: 肾小球IgG沉积与DN患者的肾小球结构改变相关, 且是DN患者肾脏预后不良的独立危险因素。此外, IgG(+)的DN患者以IgG1在GBM沉积为主, 其可能与肾脏损伤及DN进展有关。